DEVELOPMENT AND VALIDATION OF A SELECTIVE ELECTRO SPRAY IONIZATION – LIQUID CHROMATOGRAPH TANDEM MASS SPECTROMETRY METHOD FOR SIMULTANEOUS DETERMINATION OF SEMAGLUTIDE AND EMPAGLIFLOZIN IN HUMAN PLASMA - JAGAPATHI RAJU VATSAVAYI; NALANDA BABY REVU (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objective: The objective of the study was to develop a method capable of simultaneously estimating semaglutide and empagliflozin used in combination for treating Diabetes. Methods: A structured protein precipitation extraction technique was used for the estimation of semaglutide and empagliflozin. The two compounds were separated on a Zorbax C18 (50 mm × 2.1 mm, 5 μ Particle size) column, with a positive polarity Electro Spray Ionization on a Liquid chromatograph with Tandem Mass Spectrometry instrument. Verapamil was employed as an internal standard for this estimation, which was carried out through a multiple reaction monitoring method and a gradient program utilizing acetonitrile and 0.1% formic acid in water as mobile phases to achieve a separation in 2.5 min. Results: The method established was performing linearly over a working range of 1.00–1000 ng/mL for semaglutide (r2>0.98) and 0.51–500 ng/mL for empagliflozin (r2>0.98) in human plasma. The validation parameters, including specificity, selectivity, precision, accuracy, recovery, matrix effects and stability, were within acceptable limits. The stability was established in compliance with the International Council for Harmonization guideline M10 on Bioanalytical method validation. Conclusion: This method was selective and with suitable sensitivity at the 1.00 ng/mL and 0.50 ng/mL Lower Limit of Quantification employed for semaglutide and empagliflozin. It can be utilized for estimation in human plasma and will facilitate further application to bioequivalence and exploratory formulation studies for the combination of these two drugs in pharmaceutical dosage forms